Kerjasama Maritim Indonesia-Amerika Serikat sebagai Implementasi Politik Poros Maritim Indonesia: BAKAMLA-US Coast Guard - Muhammad Ridha Ridha Iswardhana (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2021)
Maritime and territorial disputes have become one of the world's main concerns, along with the awareness of the importance of the sea and the development of disputed regional issues between countries related to maritime. Reflecting on the various crime cases in the sea also accidents that caused many casualties, are certainly big concern for the importance of sea security. This research was chosen considering that the ocean is also important to be maintained, because Indonesia has focused more on development and security on land than sea. The author will use descriptive qualitative methodology wih the concept of National Interest and Maritime Security. This study found that the collaboration between the Indonesian Goverment Indonesia and the Government of the United States through Indonesian Marine Security Agency (BAKAMLA RI) and the US Coast Guad is one tangible manifestation of realizing the World Maritime Axis through security and disaster management at sea. There are various Indonesian national interests that benefit from this collaboration, including transfer of knowledge and technology, cooperation in handling illegall fishing and marine crime.